Conversations with Cinematographers - Ellis, David A. (Rowman & Littlefield Publishers, 2011)
David A. Ellis has interviewed some of the most influential and highly regarded cameramen of the last half century and more, and he has assembled these exchanges in Conversations with Cinematographers. While their names may not be known by the general public, these men and their work have left indelible imprints on the silver screen. Among those interviewed are several award-winning artists: • Douglas Slocombe (Kind Hearts and Coronets, Julia, Raiders of the Lost Ark) • Oswald Morris (The Guns of Navarone, Fiddler on the Roof, Oliver!) • Christopher Challis (A Shot in the Dark, Chitty Chitty Bang Bang, Top Secret!) • Billy Williams (Women in Love, The Wind and the Lion, Gandhi) • Freddie Francis (Sons and Lovers, The Elephant Man, Glory) • Chris Menges (The Killing Fields, The Mission, The Reader) • John De Borman (The Full Monty, Hamlet, An Education) • Gilbert Taylor (Dr. Strangelove, A Hard Day's Night, Frenzy, Star Wars) • Jack Cardiff (Black Narcissus, The Red Shoes, The African Queen) • Nicolas Roeg (Fahrenheit 451, Far from the Madding Crowd, Petulia) • Alex Thomson (Excalibur, Legend, Hamlet) • Walter Lassally (Tom Jones, Zorba the Greek, Heat and Dust) • Anthony Dod Mantle (Slumdog Millionaire, The Last King of Scotland, 127 Hours) Along with several camera operators who were also interviewed, these cinematographers recount their experiences on sets and reveal what it was like to work with some of the most acclaimed directors of all time, including Alfred Hitchcock, Fred Zinnemann, Carol Reed, John Huston, David Lynch, and Steven Spielberg. With valuable insight into the craft of moviemaking, this collection of interviews will appeal to film professors, scholars, and students, as well as anyone with an interest in the art of cinematography.